The complex vocalization of Scinax cardosoi (Anura: Hylidae), with comments on advertisement calls in the S. ruber Clade - Carvalho, Thiago Ribeiro de; Martins, Lucas Borges; Giaretta, Ariovaldo Antonio (Phyllomedusa: Journal of Herpetology, 2015)
The complex vocalization of Scinax cardosoi (Anura: Hylidae), with comments on advertisement calls in the S. ruber Clade. The complex vocalization of Scinax cardosoi from a population of Minas Gerais in southeastern Brazil is described and compared with available acoustic data for the other species of the S. ruber Clade. Three distinct types of high-pitched, pulsed calls were identified, and are referred to as “short,” “long,” and “trilled” calls. Short calls (16–66 ms) resemble squeaks, and consist of a pulsed signal (8–28 pulses/call) with regular amplitude modulations throughout their duration; the amplitude peak occurs at about the midpoint of the call duration. Long calls (268–518 ms) resemble giggles, and have lower amplitude than short calls; typically, they consist of pulsed note series (1–6 notes/call). Trilled calls resemble insect chirps and have the lowest amplitude of the three call types; they consist of long (1.1–3.0 s) pulsed note series (9–25 notes/call). Acoustic data are taxonomically informative in the Scinax ruber Clade and provide phenotypic characters diagnosing S. cardosoi in addition to those features proposed in its original description. The vocalization repertoire of S. cardosoi resembles the complex vocal repertoires (i.e., multiple call types emitted in variable combinations) of members of the S. catharinae Clade more than some species of the S. ruber Clade, which tend to have simpler call structures (i.e., a single type of multipulsed note).